2018
DOI: 10.1038/s41598-018-26199-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival Comparisons Between Early Male and Female Breast Cancer Patients

Abstract: We aimed to compare the overall survival (OS) and standardized mortality rate (SMR) of the male breast cancer (MBC) with female breast cancer (FBC) after propensity score matching. Based on the Surveillance, Epidemiology, and End Results (SEER), the early breast cancer patients (T1–2N0–2M0) were extracted from 1998–2007. This study included 1,111 and 2,151 patients with early MBC and FBC, respectively, whose clinicopathological characteristics were well balanced. At a mean follow-up time of 97 months, 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
2
8
1
Order By: Relevance
“…At our knowledge, other published studies 26 , 27 carried out propensity score matching to adjust potential confounding factors. In the series of Wang et al 28 their balanced group had a ratio of approximately two FBC to every MBC, and showed a Ten Years OS of 58.3%, with FBC with superior OS than MBC even after matching, in contrast with our findings.…”
Section: Discussioncontrasting
confidence: 91%
“…At our knowledge, other published studies 26 , 27 carried out propensity score matching to adjust potential confounding factors. In the series of Wang et al 28 their balanced group had a ratio of approximately two FBC to every MBC, and showed a Ten Years OS of 58.3%, with FBC with superior OS than MBC even after matching, in contrast with our findings.…”
Section: Discussioncontrasting
confidence: 91%
“…Most of the studies have demonstrated that the median age at diagnosis of MBC is 68 years, which is 5–10 years older than that of women when diagnosed with breast cancer (12). Moreover, black men were at a higher risk of MBC than other races (30, 31). Also, MBC patients who had undergone surgery and radiotherapy have a better prognosis (31).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, black men were at a higher risk of MBC than other races (30, 31). Also, MBC patients who had undergone surgery and radiotherapy have a better prognosis (31). The findings of our analysis are consistent with these previous reports.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, superior discriminatory capacity was observed in our nomogram compared to the SEER or TNM staging classification, with respect to OS prediction. Two other studies have also established prognostic nomograms for MBC (Sun et al, 2019; Wang et al, 2018). Sun et al (2019) established a nomogram for predicting breast cancer-specific death and other cause-specific deaths of non-metastatic MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al also established a nomogram for predicting the OS of early breast cancer patients (T 1−2 N 0−2 M 0 ). They found that age, marital status, grade, T stage, N stage, ER, surgery, chemotherapy, and radiation therapy were independent prognostic factors of OS (Wang et al, 2018). The results of their study are basically consistent with our findings; however, there are still differences between the two studies in the patients included.…”
Section: Discussionmentioning
confidence: 99%